Bacterial community dynamics in a rotating biological contactor treating 2‑fluorophenol‑containing wastewater - Duque, Anouk F. (2014)
One of the main factors affecting the performance of rotating biological contactors (RBC) is the biofilm characteristics. Therefore, a deep understanding of the microbial population dynamics and structure of the biofilm is mandatory if optimization of organic matter and nutrients removal is targeted. This study focused on the effects of organic shock loads of 2-fluorophenol (2-FP) on the microbial diversity present in an RBC biofilm. The RBC was seeded with activated sludge from a conventional wastewater treatment plant and was operated during 496 days. During the first 126 days, the RBC was subjected to intermittent 2-FP shocks of 25 mg l(-1) and no degradation occurred. Therefore, the reactor was subsequently augmented with a 2-FP-degrading strain (FP1). Afterwards, the RBC had a stable performance when subjected to 2-FP shocks up to 50 mg l(-1) and to a starvation period, as indicated by removal of the compound. Denaturing gradient gel electrophoresis (DGGE) revealed large shifts in microbial communities present in the first and fifth stages, although no clear relation between the sample collection time and spatial factor was found. Phylogenetic affiliation of some predominant members was assessed by direct sequencing of correspondent DGGE bands. Affiliations to alpha-, beta- and delta-Proteobacteria were found. Several bacterial strains isolated from the reactor showed capacity for 2-FP degradation. Strain FP1 was successfully recovered from the biofilm by plating and by DGGE, reinforcing that bioaugmentation was successfully achieved.